Modulating Signal Generation in Aptamer‐Based CNT‐FET Biosensors by Controlling the Functionalization Route - Haosen Miao; Gririraj Manoharan; Ahran Lim; Peter Mirau; Jorge L. Chávez; Chang‐Seuk Lee; Matteo Palma (Advanced Sensor Research)
Abstract The identification of biomarkers is key to the early detection of physiological dysfunction. Nanoscale field‐effect transistors (FETs) modified with target‐specific receptors enable direct target sensing, offering enhanced sensitivity due to nanoscale channel confinement. In this regard, single‐walled carbon nanotubes (SWCNTs) have emerged as strong candidates for the development of transistor‐based biosensors. Understanding the structural parameters that affect sensing performance in such nanoscale electrical detection platforms is essential for their reliable and controllable use. Here, this is investigated that how different assembly strategies employed in the construction of nanoscale aptamer‐based SWCNT‐FET biosensors can dramatically affect their signal generation, with conductance increasing or decreasing for the same aptamer‐cortisol recognition event. a cortisol‐binding DNA aptamer exhibiting well‐characterized conformational behavior is employed, as a model receptor to explore the influence of different surface functionalization strategies on SWCNT‐based biosensors performance. Through combined electrical and optical characterization, this is elucidated that how aptamer conformation governs local electrostatic changes within the Debye length, which in turn modulates the electrostatic gating of the devices. This work offers insight into effective design strategies for the construction of biosensors functionalized with electrostatically active molecular receptors.